2008
DOI: 10.1080/00346760701821979
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty and Growth in Transition Economies

Abstract: The paper investigates the relationship between fundamental uncertainty, a recurrent theme in post-Keynesian economic literature, and economic performance in transition economies. Uncertainty in the transitional economic environment is enhanced by factors such as institutional transformation, political and social instability, and legacies of the past. To capture the changes in the levels of transition-specific uncertainty, the authors have designed the uncertainty index, based on a weighted selection of Herita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…In the cases of Bulgaria, the Czech Republic, Hungary, Lithuania, Poland, Romania and Slovenia, for which we find that output growth rate reduces its uncertainty, other mechanisms must be at work to explain such a negative effect. Note that these countries have undergone major institutional transformation during the transition period, which enhanced uncertainty surrounding their economic environment (Susjan and Redek, 2008). However, transformation to free market economy increased productivity of these countries, and as a result, starting from mid-1990s these countries enjoyed relatively higher growth rate (see, e.g., Gomulka, 2000;Campos and Coricelli, 2002;Fischer and Sahay, 2000;Dibooglu and Kutan, 2005).…”
Section: Casual Relationship Among Output Growth Rate Inflation Uncementioning
confidence: 99%
“…In the cases of Bulgaria, the Czech Republic, Hungary, Lithuania, Poland, Romania and Slovenia, for which we find that output growth rate reduces its uncertainty, other mechanisms must be at work to explain such a negative effect. Note that these countries have undergone major institutional transformation during the transition period, which enhanced uncertainty surrounding their economic environment (Susjan and Redek, 2008). However, transformation to free market economy increased productivity of these countries, and as a result, starting from mid-1990s these countries enjoyed relatively higher growth rate (see, e.g., Gomulka, 2000;Campos and Coricelli, 2002;Fischer and Sahay, 2000;Dibooglu and Kutan, 2005).…”
Section: Casual Relationship Among Output Growth Rate Inflation Uncementioning
confidence: 99%
“…As a result, the index is more universal than comparable uncertainty indices (Ghirelli et al , 2019a). Because EPU is heavily influenced by policymakers and current politics in an economy (Sušjan and Redek, 2008), it is appropriate to include variables that reflect the outcome of fiscal, monetary and regulatory policy uncertainty, which are the main policies that cause the most type of policy uncertainty in news article (Baker et al , 2016). The macroeconomic variables selected in this study are CPI, broad money, trade (export of goods and import of goods), GDP and share price index (SPX).…”
Section: Data Description and Summary Statisticsmentioning
confidence: 99%
“…Asteriou and Price ( 2005 ) showed that investment uncertainty reduces the investment as well as growth in 59 industrial and developing countries between 1966 and 1992. Sušjan and Redek ( 2008 ) analyzed the nexus between uncertainty shocks and growth and showed a negative relationship between uncertainty and GDP. Christensen et al ( 2018 ) showed the possibility of greater climate changes indicating substantial higher uncertainty.…”
Section: Literature Reviewmentioning
confidence: 99%